Factors associated with risk of malnutrition in the elderly in south-eastern Brazil - Renata Damião; Álvaro da Silva Santos; Alicia Matijasevich; Paulo Rossi Menezes
ABSTRACT: Objective: The aim of this study was to evaluate the prevalence of malnutrition risk and its association with socioeconomic, behavioral, and health characteristics in the community-dwelling elderly. Methods: A cross-sectional study with individuals aged ≥ 60 years. Nutritional status was evaluated using the Mini Nutritional Assessment. Socioeconomic, behavioral, and health information was also collected from all participants. The association between each variable and the risk of malnutrition was calculated and adjusted using Poisson hierarchical regression. Results: The initial sample consisted of 3,101 elderly people, of whom 28.3% (95%CI 25.3 - 31.4%) were at risk of malnutrition. The multivariate analysis showed that the risk of malnutrition was significantly higher in women without formal education, who did not live with a partner, and identified as black-skinned. The risk of malnutrition was twice as high in individuals with no family income as compared to those who earned at least three minimum wages. Smokers were also more likely to be at risk of malnutrition than individuals who had never smoked. Participants suffering from kidney, respiratory or heart disease were at higher risk of malnutrition than those with no history of such illnesses. Conclusion: These findings could be used to help in the development of health policies and in the establishment of adequate programs aimed at reducing the risk of malnutrition in this population.